Sistem Informasi Pengelolaan dan Realisasi Dana APBDES Berbasis Website Pada Kantor Desa Pekuncen - Yani, Dwi Lusyi (TIN: Terapan Informatika Nusantara, 2021)
At the village office of pekuncen still use microsof excel to process the details of making APBDes. The APBDes is a plan in the annual finance of the village that has been established by village regulation, with a projected source of income and spending intended to support the need for a development program of the village. The metode used in system building took the waterfall model. The processing of APBDes data and the existing filing process are less effisien because it takes time. In the meantime, there is also the need for transparency around the budget and the data processing problems of the Pekuncen Village Office. Therefore, an Information System for the Management and Realization of APBDes Funds based on a website at the Pekuncen Village Office was created with the aim of being more effective and efficient in managing time and transparency in the form of realization of budget funds in the form of a special website for visitors so that the public can find out information online. System that have been devised and tested using Black Box Testing, getting the results running well as they fit